Densification of glass powder studied by master sintering curve and master kinetic curve methods - Talimian, Ali; Wondraczek, Lothar; Galusek, Dusan (International Journal of Applied Glass Science, 2021)
The master sintering curve method was applied to analyze the sintering and crystallization behavior of 15Na2O.10CaO.75SiO2 (SLS) and 17Na2O.33CaO.50SiO2 (NC2S3) glasses, in mol %. The densification of samples was successfully analyzed using the master sintering curve (MSC) method; it gives activation energy Q = 310–340 kJ.mol−1, which is in good agreement with the expected activation energy of the viscous flow. While the obtained activation energy enables predicting the sintering behavior of SLS glass, the actual results are different from the estimated data for NC2S3. The activation energy of crystallization of NC2S3, determined by constructing Master Kinetic Curves (MKC) was lower than the sintering activation energy: this impairs the prediction ability of MSC for NC2S3 glass.
CRIS-Team Scopus Importer:2023-04-20
Keywords: crystallization; sintering; soda-lime silicate